2004
DOI: 10.1074/jbc.m404331200
|View full text |Cite
|
Sign up to set email alerts
|

Krtap16, Characterization of a New Hair Keratin-associated Protein (KAP) Gene Complex on Mouse Chromosome 16 and Evidence for Regulation by Hoxc13

Abstract: Intermediate filament (IF) keratins and keratin-associated proteins (KAPs) are principal structural components of hair and encoded by members of multiple gene families. The severe hair growth defects observed upon aberrant expression of certain keratin and KAP genes in both mouse and man suggest that proper hair growth requires their spatio-temporally coordinated activation. An essential prerequisite for studying these cis-regulatory mechanisms is to define corresponding gene families, their genomic organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 40 publications
3
38
0
2
Order By: Relevance
“…cDNA suppression subtraction hybridization (18). Both KAP genes were identified as members of a novel KAP gene domain on MMU16 in a region of conserved linkage to HSA21q22.11 (18,22), and most of the cDNAs isolated by suppression subtraction hybridization in the previous study corresponded to this domain (18,22), a bias that was not observed in the DNA microarray data set presented here. The up-regulation of Krt2-1 in the epidermis (Table 1) was also noted in the previous screen (18), and although this finding is consistent with the epidermal hyperproliferation and ichthyosiform condition observed in GC13 mice, a potential mechanistic link to the overexpression of Hoxc13 in hair follicles is currently obscured since epidermal Hoxc13 expression was not detectable by ISH in both normal and GC13 mice (data not shown).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…cDNA suppression subtraction hybridization (18). Both KAP genes were identified as members of a novel KAP gene domain on MMU16 in a region of conserved linkage to HSA21q22.11 (18,22), and most of the cDNAs isolated by suppression subtraction hybridization in the previous study corresponded to this domain (18,22), a bias that was not observed in the DNA microarray data set presented here. The up-regulation of Krt2-1 in the epidermis (Table 1) was also noted in the previous screen (18), and although this finding is consistent with the epidermal hyperproliferation and ichthyosiform condition observed in GC13 mice, a potential mechanistic link to the overexpression of Hoxc13 in hair follicles is currently obscured since epidermal Hoxc13 expression was not detectable by ISH in both normal and GC13 mice (data not shown).…”
Section: Discussionmentioning
confidence: 77%
“…7, A and B). Hoxc13-oligo complex formation was inhibited by HOXC13-specific antiserum (21), which reacts specifically with mouse Hoxc13 in both supershift and immunohistochemical assays (22,36), whereas anti-tyrosinase-related protein 1 antiserum (see "Materials and Methods") used as a control did not affect complex formation (Fig. 7B).…”
Section: Effects Of Foxq1 Sa (Satin) Allele On Expression Of Medullasmentioning
confidence: 96%
See 2 more Smart Citations
“…With such a technique, Hedlund et al (Hedlund et al, 2004) identified candidate target genes by comparing embryonic spinal cord tissue from wild-type and Hoxd10-null mice. In a related approach, Pruett et al (Pruett et al, 2004) used transgenic mice overexpressing the Hoxc13 gene to identify keratin genes of the Krtap16 family as likely direct targets of HOXC13. The use of such approaches is nevertheless complicated by the severity of some Hox mutations and the functional redundancy of these genes.…”
Section: Introductionmentioning
confidence: 99%